Standard Volume Tables Por Gmelina arborea Roxb. (Based on Data from Tripura) - Sharma, R. P.; Jain, R. C. (Indian Forester, 1977)
Timber and Total Wood Volume based on the regression equation V = a+ b D2H have been computed. Variation ia volume has been well explained by the character D2H.